2007
DOI: 10.1074/jbc.m701660200
|View full text |Cite
|
Sign up to set email alerts
|

The Shuttling SR Protein 9G8 Plays a Role in Translation of Unspliced mRNA Containing a Constitutive Transport Element

Abstract: The splicing regulatory SR protein, 9G8, has recently been proposed to function in mRNA export in conjunction with the export protein, Tap/NXF1. Tap interacts directly with the Mason-Pfizer monkey virus constitutive transport element (CTE), an element that enables export of unspliced, intron-containing mRNA. Based on our previous finding that Tap can promote polysome association and translation of CTE-RNA, we investigated the effect of 9G8 on cytoplasmic RNA fate. 9G8 was shown to enhance expression of unsplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 73 publications
2
92
0
Order By: Relevance
“…However, other proteins may be limiting in this situation, and the stable recruitment of TAP to mRNA may require factors such as U2AF or the Cap-binding complex. Interestingly, 9G8 has recently been shown to enhance expression of genes containing a constitutive transport element (CTE) (31), which may arise through enhanced TAP-CTE interaction. Clearly, further experiments are required to resolve this issue and further establish whether loss of an export adaptor…”
Section: Discussionmentioning
confidence: 99%
“…However, other proteins may be limiting in this situation, and the stable recruitment of TAP to mRNA may require factors such as U2AF or the Cap-binding complex. Interestingly, 9G8 has recently been shown to enhance expression of genes containing a constitutive transport element (CTE) (31), which may arise through enhanced TAP-CTE interaction. Clearly, further experiments are required to resolve this issue and further establish whether loss of an export adaptor…”
Section: Discussionmentioning
confidence: 99%
“…SRSF7 recognizes CTEs of virus mRNAs through its RRM domain, and contributes to translational activation of these mRNAs as well as mRNA export of them (20,36). A subset of RNA-binding proteins, SRSF3 and RBM4, regulate translational activity of their targeted mRNAs through binding to 5'UTR of them (22,27).…”
Section: Discussionmentioning
confidence: 99%
“…SRSF7 shuttles constantly between the nucleus and cytoplasm (10), and contribute to the export of certain viral and cellular mRNAs through directly binding to transporter 1 (TAP)/nuclear RNA export factor 1 (NXF1), an essential mRNA export factor (16,20,21,32). In addition, overexpression of SRSF7 enhanced the association of polyribosome with a structured RNA sequence, termed the constitutive transport element (CTE), which recruits TAP/NXF1 (36).…”
Section: Introductionmentioning
confidence: 99%
“…shown that expression and translation of the GagPol produced from this reporter can be monitored by measuring the accumulation of HIV p24 in the supernatant of the transfected cells (Smith et al 1990;Bray et al 1994;Guzik et al 2001;Coyle et al 2003;Jin et al 2003;Bor et al 2006;Li et al 2006;Swartz et al 2007). Such expression is absolutely dependent on the presence of a cis-acting element, either a CTE or an RRE.…”
Section: Knockdown Of Tpr Increases Protein Expression From a Cte-conmentioning
confidence: 99%